Assessing the effect of health status on multidimensional poverty among older adults: the Chinese longitudinal healthy longevity survey - Zhou, Lulin; Zhu, Change; Walsh, Christine A.; Zhang, Xinjie (Frontiers in Public Health, 2023)
Background This study aimed to explore the association between health status (physical, mental, and self-rated health) and multidimensional poverty (subjective and objective poverty) in older adults. Method A panel binary logit regression approach was applied to four waves of CLHLS data (2008, 2011, 2014, and 2018). In total,1,445 individuals were included after data cleaning. Results The mean values and proportion of physical, mental, and self-rated health were 5.73 (87.42%), 0.93 (93.06%), and 3.46 (86.7%), respectively, and mean values and proportion of subjective and objective poverty were 0.19 (18.51%) and 0.21(21.4%). In addition, physical, mental, and self-rated health were all found to be associated with subjective poverty among older adults (r = −0.181, r = −0.630, r = −0.321, p < 0.05), that is, the better the physical, mental, and self-rated health, the lower the probability of subjective poverty. A comparable connection between self-rated health and objective poverty also exists (r = −0.157, p < 0.05). Furthermore, medical expenditure played a mediation role in the association between the health status and poverty of older adults. Conclusion In order to effectively alleviate the poverty of older adults, strategies should be taken to improve the health level of older adults, especially the physical and mental health of high-aged older adults, and the self-rated health of middle-aged older adults. Furthermore, social security and pensions should be further developed to adequately reimburse medical expenditures.